Adsorption and heat characteristics of coal‒microorganisms during the cogeneration of H2 and CH4 following pretreatment with white rot fungi. (10th May 2020) - Xia, Daping; Zhang, Huaiwen; Su, Xianbo; Deng, Ze; Wang, Qian
Abstract: To investigate the adsorption and heat characteristics of coal‒microorganisms during the cogeneration of hydrogen (H2 ) and methane (CH4 ), fermentation experiments of biogas production were conducted using highly volatile bituminous coal from the Yima coalfield, China. The coal samples pretreated with white rot fungi (WRF) were the experimental group (EG), and original untreated coal samples were the control group (CG). The microbial adsorption characteristics and adsorption heat were measured using ultraviolet spectrophotometry and micro-calorimetry, respectively. The results showed the following: (1) The total hydrogen yield in the EG and CG was 1.32 mL/g and 6.64 mL/g, respectively, and the total methane production in the EG and CG was 5.78 mL/g and 2.75 mL/g, respectively. Moreover, the hydrolysis stage (methanogenesis) in the EG was significantly shorter than that in the CG, and the gas production cycle was prolonged. (2) The cogeneration process of H2 and CH4 was an exothermic reaction, except the CG in the hydrogen production phase. The adsorption capacity (AC) of coal‒microorganisms was larger, and the heat output (HO) was higher. (3) The maximum AC and HO in the EG and CG were 2000 μg and 84.344 J/g, 2364 μg and 57.467 J/g, respectively, during hydrogen generation. The maximum value of AC and HO in the EG and CG were 2227 μg and 70.216 J/g, 1931 μg and 20.056 J/g, respectively, during methane generation. (4) A negative correlation between the contents of organic compounds and HO and AC was observed in the hydrogen production phase. However, methanogenesis showed the opposite results, and the quantity and types of total organic compounds were significantly greater than that those in the hydrogen production phase. (5) Pseudomonas was the dominant genus in the EG and CG in the hydrogen production phase and hydrolysis phase of methanogenesis. Methanobacterium was the dominant genus in the EG and CG at the end of methane production. This research not only enriches the theory of biogas production from coal, but also demonstrates the advantages of biological pretreatment and fermentation cogeneration, which may improve overall energy utilization, and optimize the gas generation process. Highlights: Based on experiments, the adsorption and heat characteristics of coal‒microorganisms are analyzed. The gas production cycle was prolonged after double pretreatment with white rot fungi and hydrogen production. The cogeneration process of H2 and CH4 was an exothermic reaction. The adsorption capacity of coal‒microorganisms was larger, and the heat output was higher.